A stepwise, 'test-all-positives' methodology to assess gluten-kernel contamination at the serving-size level in gluten-free (GF) oat production. (1st February 2018) - Chen, Yumin; Fritz, Ronald D.; Kock, Lindsay; Garg, Dinesh; Davis, R. Mark; Kasturi, Prabhakar
Highlights: Gluten free claim compliance at the serving-size level provides the best protection. Gluten free oats under Purity Protocol found 4% non-compliant at serving-size level. Non-homogenous grinding dictates a reliable way to assess gluten compliance in oats. Analytical scheme proposed and verified to assess gluten in gluten-free oats. Abstract: A step-wise, 'test-all-positive-gluten' analytical methodology has been developed and verified to assess kernel-based gluten contamination (i.e., wheat, barley and rye kernels) during gluten-free (GF) oat production. It targets GF claim compliance at the serving-size level (of a pouch or approximately 40–50 g). Oat groats are collected from GF oat production following a robust attribute-based sampling plan then split into 75-g subsamples, and ground. R-Biopharm R5 sandwich ELISA R7001 is used for analysis of all the first15-g portions of the ground sample. A >20-ppm result disqualifies the production lot, while a >5 to <20-ppm result triggers complete analysis of the remaining 60-g of ground sample, analyzed in 15-g portions. If all five 15-g test results are <20 ppm, and their average is <10.67 ppm (since a 20-ppm contaminant in 40 g of oats would dilute to 10.67 ppm in 75-g), the lot is passed.